Analytical assessment of current insurance as part of management of consequences of emergencies - K.Yu. Polyak (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article examines the current state of the insurance system as a component of managing the consequences of emergencies. The researches are presented in the following areas: the insurance against accidents and fire risks and risks of natural disasters; property insurance (property, goods and agricultural products); the insurance of transport (by modes); liability insurance (by liability). So, the author made the statistical and analytical assessment of consequences of emergencies that was learned through the study of modern insurance system, which enabled to identify the complex of accounting objects in the management of consequences of emergencies.